PENDAMPINGAN UMKM BERBASIS DIGITAL MARKETING UNTUK MENINGKATKAN KEUNGGULAN KOMPETITIF PRODUK DI DESA SUMBERBULU - Loviga Denny Pratama; Anisa Yulia Putri; Novi Ayu Yulia; Wahyu Lestari (Universitas Mataram, 2022)
Digital media can support Micro, Small and Medium Enterprises (MSMEs) to increase brand awareness of their products, so they can gain competitive advantage and reach a wider market. However, not all MSME actors have the ability to use digital media to support their business. One of them is for SMEs in Sumberbulu Village, Probolinggo Regency. This Community Service is carried out with Zainul Hasan Islamic University students through the Community Service Program. The purpose of this program is to increase the knowledge and skills of MSMEs about creative digital marketing strategies and their understanding of the market so that they can create online stores for their businesses. The method of community service uses the ABCD (Asset-Based Community-driven Development) method. The result of this community service is that MSME actors in Sumberbulu Village are able to create online stores. So that they can promote their products through the marketplace and social media and ultimately increase their income. Through online stores, it is also possible for MSME actors in Sumberbulu Village to expand their market reach. In addition, the output of this community service activity is the design of MSME product packaging and websites. It can be concluded that in this program, in addition to implementing the tri dharma of higher education, this community service also helps government programs in encouraging MSME actors to be able to compete in the global market so that they can prosper the surrounding community.